Insights on Sustainability of Small and Medium Enterprises in Oman: A Conceptual Framework - Alqassabi, Mohammed Ali (International Journal of Economics and Financial Issues, 2020)
This paper provides insights on the sustainability of SMEs in Oman and presents a conceptual framework for the government support to the SMEs. The paper adopted a sequential mixed method of interviews and structured questionnaire including 390 SMEs. Non-parametric techniques of chi-square test and spearman rank correlation were used. The challenges facing SMEs in Oman include: the rules and regulations of doing business, the competition, and the lack of access to finance. The study also found that there is a positive correlation between government support and sustainability of SMEs in Oman. From the perspective of the government, supporting the SMEs is strategic to diversity the national economy and reduce the unemployment among the youths. This support includes marketing, financial, advisory, management, technical and infrastructural. However, many of the owners of the SMEs were not aware of these supports and raised issues regarding the procedures, laws, regulation and sufficiency of these supports. Keywords: SMEs, Sustainability, Government Support, Non-parametric methods, Oman JEL Classifications: E24, G38, L26 DOI: https://doi.org/10.32479/ijefi.9063